Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Gender and climate change: An introduction - Dankelman, Irene (Routledge, 2010)
Bien que le changement climatique affecte tout le monde, il n'est pas neutre du point de vue du genre. Il a des répercussions sociales importantes et amplifie les inégalités existantes, notamment la disparité entre les femmes et les hommes en termes de vulnérabilité et de capacité à faire face à ce phénomène mondial. Ce nouveau manuel, édité par l'un des auteurs de l'ouvrage phare Les femmes et l'environnement dans le tiers monde : une alliance pour l'avenir (1988), qui a été le premier à exposer les liens entre la dégradation de l'environnement et les impacts inégaux sur les femmes, offre une introduction complète aux aspects sexistes du changement climatique. Plus de 35 auteurs ont contribué à l'ouvrage. Il commence par un bref historique de la pensée et de la pratique autour du genre et du développement durable au cours des dernières décennies. Il fournit ensuite un cadre théorique pour analyser les manifestations et les politiques du changement climatique du point de vue du genre et de la sécurité humaine. S'appuyant sur de nouvelles recherches, les effets réels et potentiels du changement climatique sur l'égalité des sexes et la vulnérabilité des femmes sont examinés, tant dans les contextes ruraux qu'urbains. Cela est illustré par une riche gamme d'études de cas du monde entier et de précieuses leçons sont tirées de ces expériences réelles. Les femmes sont trop souvent considérées comme des victimes du changement climatique et leur rôle positif en tant qu’agentes du changement et contributrices aux stratégies de subsistance est négligé. L’ouvrage conteste cette caractérisation et fournit de nombreux exemples de la manière dont les femmes du monde entier s’organisent, renforcent leur résilience et s’adaptent au changement climatique, ainsi que du rôle qu’elles jouent dans l’atténuation du changement climatique. La dernière partie examine les progrès réalisés en matière d’intégration de la dimension de genre dans l’atténuation et l’adaptation au changement climatique, les cadres politiques en place et la manière dont nous pouvons passer de la politique à l’action efficace. Accompagné d’un large éventail de références et de ressources clés, cet ouvrage offre aux étudiants et aux professionnels une introduction essentielle et complète aux aspects sexistes du changement climatique.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; environnement; histoire et politique; justice climatique; politiques publiques; projet charge mentale; périodes historiques; santé; science politique; science politique et droit; thématiques

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (Women and indigenous studies series, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry -- Indigenous feminism -- is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays -- What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? -- cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."--Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."-- Résumé de l'éditeur.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires